The prevalence of psychiatric disorders in general hospital inpatients: a systematic umbrella review - van Niekerk, M; Walker, J; Hobbs, H; Magill, N; Toynbee, M; Steward, B; Harriss, E; Sharpe, M (Elsevier, 2022)
Background To inform the future development of Consultation-Liaison (C-L) Psychiatry services we need accurate information on the prevalence of psychiatric disorders in the general hospital inpatient setting. Systematic reviews have summarized the literature on specific aspects of this broad topic, but there has been no high-level overview that aggregates their findings and identifies gaps in the relevant literature. We therefore aimed to produce a comprehensive overview of the field, summarizing the research literature on the prevalence of psychiatric disorders (that is, interview-based psychiatric diagnoses) in general hospital inpatients. We did this using a systematic umbrella review (systematic review of systematic reviews), which is the best and most efficient method for summarizing a broad area of research.